Analisa Kepadatan Tanah Menggunakan Sand Cone pada Peningkatan Struktur Tanggul Pantai di Kota Pekalongan - Wicaksana, Alfarizt; Wibowo, Gurawan Djati (Universitas Ibn Khaldun, 2024)
Coastal embankments are structures built along the coastline with the aim of protecting coastal areas from longshore transport. Soil compaction testing aims to determine the maximum density of a type of soil by means of impact. Increasing soil density can be done by various methods, one of which is the Sand Cone method. Sand Cone method is very important in determining the type of soil used in construction and as a guide in calculating the strength and stress required in the coastal embankment structure. The research method in this paper is quantitative. The direct shear strength test obtained normal stress results with samples 1, 2 and 3 sequentially of 24.4 kPa, 48.8 kPa, and 73.2 kPa. Shear stress results with samples 1, 2 and 3 were 24.5 kPa, 41.2 kPa, and 55.9 kPa respectively. With soil samples 1, 2 and 3 loaded with 8kg, 16kg, and 24kg respectively. It can be concluded that the soil is categorised as sandy gravel type soil and is solid. Atterberg Limit testing obtained a liquid limit value of 52.90%, Plastic Limit 32.69%. and Plasticity Index of 20.21% can be concluded to be a type of clay. Soil compaction test results obtained moisture content of 36.21%, wet volume weight of 1.63 gr / cm3, specific gravity of 2.553, optimum moisture content of 35.80%, and maximum dry weight content of 1.26 gr / cm3.